Strategic Insights and Sectoral Analysis of the Import and Export Industry: A Comprehensive Case Study of Superior Computronics Private limited - Agarwal, Jaansi (ATLAS SkillTech University, 2025)
Global trade has seen significant growth driven by globalization, technological advancements and reduction of trade barriers. Countries like China, India and Brazil are increasingly becoming significant players in international trade.
Project Report on Strategic Insights and Sectoral Analysis of the Import and Export Industry: A Comprehensive Case Study of Superior Computronics Private limited (2023-2025) Under the Guidance of Prof. Cleston D'Costa
Keywords: globalization; Global trade; international trade